Regional growth and finance in Europe: Is there a quality effect of bank efficiency? - Hasan, Iftekhar; Koetter, Michael; Wedow, Michael (Journal of Banking & Finance, 2009)
In this study, we test whether regional growth in 11 European countries depends on financial development and suggest the use of cost- and profit-efficiency estimates as quality measures of financial institutions. Contrary to the usual quantitative proxies of financial development, the quality of financial institutions is measured in this study as the relative ability of banks to intermediate funds. An improvement in bank efficiency spurs five times more regional growth then an identical increase in credit does. More credit provided by efficient banks exerts an independent growth effect in addition to direct quantity and quality channel effects.